Byssogenesis of Green Mussel Perna viridis as a Biomarker of Microplastic Pollution - Novianti Utami Rahmat; Khusnul Yaqin; Sri Wahyuni Rahim (JURNAL PERIKANAN DAN KELAUTAN, 2020)
The presence of microplastic in the enviroment is a problem because they are persistent and they are consumed by organisms. Microplastic will affect aquatic life as a result various types of contamination in the aquatic enviroment can enter the body of green mussel. The ability to develop mussel is determined by the strength of the byssus. Utilization of green mussel byssus as biomarker to detect microplastic pollution is still a rare thing to do. The purpose of this study is to know the microplastic effect on the production off green mussel byssus. Green mussel with lengths of 4.1 - 5.0 cm were collected from Maccini Baji Water, Labakkang District, Pangkep Regency. The experimental desigh used is a Completely Randomized Design exposure was carried out for 7 days with microplastics concentration namely 0, 0.05, 0.5 and 5 g/L using polyethylene microplastics usually used as a raw material for scrub bath. The results of study show that production of green mussel byssus exposed at all concentration on day 1-6 were not significantly different at all concentration, but 7 days there significantly different 0 g/L treatment 0 g/L from 5 g/L. This mean that the green mussel byssus can be used as a microplastic pollution biomarker with a testing duration of 7 days